Bahamas constitution : options for change (The Government of The Bahamas Nassau, 2003)
Summarizes and simplifies the major provisions of the constitution. Highlights some of the perceived deficiencies and alerts readers to possibilities for the amendment and reform of the constitution.
Keywords: CONSTITUTIONS